2015
DOI: 10.1007/s10519-014-9704-4
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and Environmental Contributions to the Relationships Between Brain Structure and Average Lifetime Cigarette Use

Abstract: Chronic cigarette use has been consistently associated with differences in the neuroanatomy of smokers relative to nonsmokers in case-control studies. However, the etiology underlying the relationships between brain structure and cigarette use is unclear. A community-based sample of male twin pairs ages 51-59 (110 monozygotic pairs, 92 dizygotic pairs) was used to determine the extent to which there are common genetic and environmental influences between brain structure and average lifetime cigarette use. Brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
1
21
1
Order By: Relevance
“…Previous studies have reported association between tobacco usage and volume of left thalamus (Gallinat et al, 2006; Gillespie et al, 2018; Hanlon et al, 2016), which might be due to faster age related volume loss in smokers (Durazzo et al, 2017). We did not replicate other cortical or subcortical associations previously reported (Gallinat et al, 2006; Hanlon et al, 2016; Prom-Wormley et al, 2015). Alcohol intake was also associated with left thalamus thickness in the UKB, consistent with the significant grey-matter correlation ( Figure 2 ) between the two traits.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported association between tobacco usage and volume of left thalamus (Gallinat et al, 2006; Gillespie et al, 2018; Hanlon et al, 2016), which might be due to faster age related volume loss in smokers (Durazzo et al, 2017). We did not replicate other cortical or subcortical associations previously reported (Gallinat et al, 2006; Hanlon et al, 2016; Prom-Wormley et al, 2015). Alcohol intake was also associated with left thalamus thickness in the UKB, consistent with the significant grey-matter correlation ( Figure 2 ) between the two traits.…”
Section: Discussioncontrasting
confidence: 99%
“…In these analyses, only bi-allelic SNPs with minor allele frequencies of at least 1% were retained. Tests for association used linear regression assuming an additive allelic effect, treating each topic pulmonary disease, as well as multiple apparently novel disease loci for pregnancy complications, viral susceptibility, anemia/fracture risk and uterine cancer not previously associated at a genome-wide threshold with disease (based on searching the National Human Genome Research Institute-European Bioinformatics Institute Catalog of published genome-wide association studies) (25). We compared our results to those arising from a standard singlediagnostic-code PheWAS; this approach would not have yielded association at this threshold.…”
Section: Discussionmentioning
confidence: 99%
“…For example, small, widespread negative associations were recently reported between cigarette pack-years and the volume and/or surface area of several cortical as well as subcortical brain structures (Prom-Wormley et al, 2015). Importantly, correlations were the result of shared genetic and unique environmental factors in brain structures involved in the processing of environmental influences related to smoking.…”
Section: Twin and Family Studies Of Substance Use Disordermentioning
confidence: 99%